5(k-5)-4(k+1)-13=-33

Simple and best practice solution for 5(k-5)-4(k+1)-13=-33 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(k-5)-4(k+1)-13=-33 equation:


Simplifying
5(k + -5) + -4(k + 1) + -13 = -33

Reorder the terms:
5(-5 + k) + -4(k + 1) + -13 = -33
(-5 * 5 + k * 5) + -4(k + 1) + -13 = -33
(-25 + 5k) + -4(k + 1) + -13 = -33

Reorder the terms:
-25 + 5k + -4(1 + k) + -13 = -33
-25 + 5k + (1 * -4 + k * -4) + -13 = -33
-25 + 5k + (-4 + -4k) + -13 = -33

Reorder the terms:
-25 + -4 + -13 + 5k + -4k = -33

Combine like terms: -25 + -4 = -29
-29 + -13 + 5k + -4k = -33

Combine like terms: -29 + -13 = -42
-42 + 5k + -4k = -33

Combine like terms: 5k + -4k = 1k
-42 + 1k = -33

Solving
-42 + 1k = -33

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '42' to each side of the equation.
-42 + 42 + 1k = -33 + 42

Combine like terms: -42 + 42 = 0
0 + 1k = -33 + 42
1k = -33 + 42

Combine like terms: -33 + 42 = 9
1k = 9

Divide each side by '1'.
k = 9

Simplifying
k = 9

See similar equations:

| x=x^2-4x+2 | | Y=2t+1 | | .5x-7=0.1(x+10) | | -6(2w+1)-w=33 | | .5x-7=.1(x+10) | | 7x-11=16-2x | | -6x-3x-15=-9-2x | | 8=-4(c+6) | | 2x+(2y-164)=992 | | 36-3(2w+1)=9w-3(w+2) | | 15-7x=1-5x | | 16x+8y=-28 | | 5(2*3-3)= | | 5h=-60 | | -7x+10+8x=5+x+5 | | 2y-9=8y+21 | | y-6y=9+6 | | 7x+1x-9=2(4x+9) | | 15x-6=35x+2 | | 3w=3+15 | | 12+6x=72 | | 20x+12y=480 | | f(-6)=(x-1)2+3 | | 11n+3= | | 3z^2-8z-78=6z+2 | | f(x)=(x-1)2+3 | | 2d^2+12d+13=-2+d | | 19n+16n+167=1132 | | 9x+3=x+3 | | (x^2)-10+25=0 | | X+(x+36)=90 | | 20x+16y=480 |

Equations solver categories